Adoption of a the digital decision support tool Rice Crop Manager (RCM) by the government of the Philippines - CGIAR Research Program on Rice (2021)
Following the launch of RCM, DA-PhilRice, IRRI with funding support from the DA-Bureau of Agricultural Research (DA-BAR) and DA-Agricultural Training Institute (DA-ATI) have worked closely together to expand the tool’s capabilities to provide advisory services. The offical transition of RCM to the DA is a signifciant step in scaling.